The effect of social media, product availability, and prices on the purchasing decision to opt continuing study at University of Muhammadiyah Tangerang - Komalasari, Een; Susilo, Priyo; Gumilar, Aris (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2023)
This research is a typical of associative research which conducted through quantitative approach. This research aims to figure out things in relation to the effect of social media, product availability, and price on purchasing decision to opt continuing study at University of Muhammadiyah Tangerang. The total 300 samples in this research had been selected through simple random sampling technique out of the total number of populations. The data has been analyzed by using multiple linear regression. Based on the research conducted, there have been found several findings; 1) Social media, partially, has a positive effect on the decision-making for students to opt University of Muhammadiyah Tangerang as the educational institution to continue their higher education degree; 2) Product availability, partially, has a positive effect on the decision-making for students to opt University of Muhammadiyah Tangerang as the educational institution to continue their higher education degree; 3) Price, partially, has a negative effect on the decision-making for students to opt University of Muhammadiyah Tangerang as the educational institution to continue their higher education degree; and 4) Simultaneously, social media, product availability, and price, are capable of giving effect to Y variable for 92.7%. The remaining 7.3% is affected by other factors outside the variables under study, such as promotion, service quality, brand image, and others